2000
DOI: 10.1073/pnas.97.3.1202
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone reduces neuronal secretion of Alzheimer's β-amyloid peptides

Abstract: Alzheimer's disease (AD) is characterized by the age-related deposition of ␤-amyloid (A␤) 40͞42 peptide aggregates in vulnerable brain regions. Multiple levels of evidence implicate a central role for A␤ in the pathophysiology of AD. A␤ peptides are generated by the regulated cleavage of an Ϸ700-aa A␤ precursor protein (␤APP). Full-length ␤APP can undergo proteolytic cleavage either within the A␤ domain to generate secreted s␤APP␣ or at the N-and C-terminal domain(s) of A␤ to generate amyloidogenic A␤ peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(157 citation statements)
references
References 21 publications
6
151
0
Order By: Relevance
“…Epidemiological studies indicate that AD is more common in females than in males, and the underlying mechanism for this sex difference has been proposed to involve the higher levels of estrogen in females (Manthey et al, 2001;Zhang et al, 2005). Another explanation may be that because males express more testosterone this leads to reduction in levels of Aβ since it has been demonstrated that testosterone reduces Aβ production (Gouras et al, 2000). Interestingly, we found that male 3xTgAD mice exhibited many more tau immunoreactive CA1 and amygdalar neurons compared to females.…”
Section: Discussionmentioning
confidence: 48%
“…Epidemiological studies indicate that AD is more common in females than in males, and the underlying mechanism for this sex difference has been proposed to involve the higher levels of estrogen in females (Manthey et al, 2001;Zhang et al, 2005). Another explanation may be that because males express more testosterone this leads to reduction in levels of Aβ since it has been demonstrated that testosterone reduces Aβ production (Gouras et al, 2000). Interestingly, we found that male 3xTgAD mice exhibited many more tau immunoreactive CA1 and amygdalar neurons compared to females.…”
Section: Discussionmentioning
confidence: 48%
“…16). For instance, in cells overexpressing APP, cholesterol depletion-induced sAPP␣ secretion is accompanied by a decrease of A␤ production (54). However, other studies failed to demonstrate any association between sAPP␣ secretion and A␤ generation both in vivo and in vitro (55).…”
Section: Analysis Of the Signaling Pathways Involved In The H5-ht 4(ementioning
confidence: 97%
“…17␤-estradiol at concentrations between 2 and 2000 nM increases ␣-A␤PPs production and reduces the generation of A␤ in both mouse and human cell lines and primary cultures of rat, mouse, and human embryonic cerebrocortical neurons (52)(53)(54)(55). Likewise, testosterone treatment (200 -2000 nM) of mouse neuroblastoma cells and rat primary cerebrocortical neurons increases secretion of ␣-A␤PPs and decreases the secretion of A␤ (56). Ovariectomy, which suppresses serum estrogen levels, also has been shown to increase total A␤ concentrations in guinea pigs (18) and A␤PP transgenic mice (19).…”
Section: Contribution Of Sex Steroids and Gonadotropins To Amyloidosis-mentioning
confidence: 99%